Profiles of innate immune receptors and cytokines in peripheral blood mononuclear cells in children with measles - Cao, Ling-feng (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2013)
OBJECTIVE: The aim of this study was to explore the roles and clinical significance of innate immune receptors and cytokine in children with measles